Relationship between occupation and education with the choice of IUD contraception in Pauh District, Padang City, West Sumatra. - Fitri Khoiriyah; Ariadi; Yusrawati; Laila Rahmi (Science Midwifery, 2022)
High population growth is a significant problem faced by the Indonesian people in the field of population. Efforts to create quality families are primarily targeted at controlled population growth and increasing the quality of small families, as indicated by the increased use of rational, effective, and efficient contraceptive methods, namely the use of Long-Term Contraceptive Methods (MKJP). Referring to the 2020-2024 BKKBN Strategic Plan, the BKKBN vision has been set: "Creating quality families and balanced population growth to support the achievement of an advanced Indonesia that is sovereign, independent, and has a personality based on mutual cooperation" (BKKBN, 2021). The purpose of this research was to determine the relationship of education and occupation with the selection of IUD contraceptives in the work area of ​​Pauh Health Center. This research was a cross-sectional comparative. The populations in this research were all women of childbearing age (WUS), current family planning acceptors aged 15-49 years who used IUD and non-IUD contraception. The samples of this research were 49 IUD users and 149 non-IUD users. The instruments were a questionnaire. The bivariate analysis used Chi-Squere. The results the bivariate study found that there was a not significant relationship between occupation with the selection of IUD contraceptives (p = 0.251) and there was a significant relationship between education and the selection of IUD contraceptives (p = 0.001) This study concludes that there is no relationship between occupation with the choice of IUD contraceptives and there is a relationship between education and the choice of IUD contraceptives